Now you see them, now you don’t: Professional recognition of specialist professionals working with Deaf British Sign Language parents in child safeguarding - Oram, Rosemary; Young, Alys; Cartney, Patricia (Qualitative social work : QSW : research and practice, 2024)
This paper concerns parenting assessments which are integral to child-safeguarding professional processes in England, and which involve Deaf parents whose primary language is British Sign Language (BSL). In an under-researched area of social work, the research aim was to contribute to the existing literature by eliciting the practice wisdom of specialist professionals. Specifically, it draws upon their linguistic and cultural knowledge of the Deaf community when they are involved in parenting assessments with Deaf parents who are subject to safeguarding concerns. Data about these professionals’ actual experiences of navigating Deaf cultural-competency in contemporary child protection practices were collected through seven video-recorded, semi-structured interviews conducted in BSL. Using interpretive phenomenological analysis, data were analysed in their source language (BSL). This article focusses on one key theme, termed ‘Professional Recognition’, which incorporates a) the identification of specialist roles and b) the impact of referral processes and protocols on assessment outcomes. The findings highlight participants’ perspectives on the benefits and disadvantages of their specialist role in this context. Although their brokerage skills, cultural competence, linguistic fluency and specialist knowledge of the Deaf community are highly regarded and valued by some colleagues, there is insufficient recognition of their existence by the majority. Secondly, participants are concerned by the inefficiency and inconsistency of the referral processes and protocols which they consider have adverse effects on assessment outcomes, and consequently the parents involved. The BSL translation of this article is available in the supplementary material.